2019
DOI: 10.1097/md.0000000000017100
|View full text |Cite
|
Sign up to set email alerts
|

Using weighted gene co-expression network analysis to identify key modules and hub genes in tongue squamous cell carcinoma

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Numerous studies have reported hub genes as playing key roles in cancer ( Chen et al, 2017 ; Das et al, 2017 ; Yin et al, 2019 ). To identify the hub lncRNAs and miRNAs in our synergistic network, we computed a degree for each node and sorted them in a descending order.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have reported hub genes as playing key roles in cancer ( Chen et al, 2017 ; Das et al, 2017 ; Yin et al, 2019 ). To identify the hub lncRNAs and miRNAs in our synergistic network, we computed a degree for each node and sorted them in a descending order.…”
Section: Resultsmentioning
confidence: 99%
“… 41 , 43 Moreover, AIMP2-DX2, one of variant splicing isoform of AIMP, was significantly associated with the tumorigenesis, cancer cell proliferation, invasion, and migration in many cancers, including lung cancer, ovarian cancer, and nasopharyngeal carcinoma 44 - 47 In the study of Yin K et al, elevating the expression of AIMP2 splicing variation could shorten the survival of patients with tongue squamous cell carcinoma, which was also in high accordance with our study. 48 Taken together, AIMP2 may also serve as a novel therapeutic target of SKCM.…”
Section: Discussionmentioning
confidence: 99%
“…First, the correlation of all gene pairs was calculated to construct a similarity matrix. Second, the soft threshold β was a weighted parameter of the adjacent function, which the optimal value was obtained by the pickSoftThreshold function in the R package WGCNA [ 15 ]. Third, the TOM similarity function was used to convert the adjacency value into a TOM matrix.…”
Section: Methodsmentioning
confidence: 99%